Wie hängen die Mathematikleistungen von Neuzugewanderten mit Herkunftsregion und Schulbesuchsdauer zusammen? Ergebnisse eines sprachentlasteten Tests (mathematica didactica, 2019)
Except for some case studies, only few empirical findings exist on the subject matter achievement of immigrants who newly arrived in Germany. As a contribution for reducing this research gap, the article reports on a study on the mathematics achievement of n = 176 newly arrived adolescents. The study draws upon a language-reduced, strongly differentiated test and investigates the connections of mathematics achievement to important background factors. According to the analysis of variance, the mathematics achievements of newly arrived immigrants appears to be most connected to their region of origin and their years of previous schooling. However, the groups sampled according to these factors reveal a huge heterogeneity in themselves. When compared to a sample of resident students with comparable years of previous schooling and socioeconomic status, the newly arrived immigrants do not differ substantially from immigrants of second generation.